Key wood macroscopic identification of 110 species Northern Caribbean of Costa Rica - Araya-Montero, Miguel (2013)
The Northern region of Costa Rica Caribbean supplies approximately 14 % of the wood market, using about 165 species. However this region lacks an instrument to help identify wood species, which could help to forest control to the Costa Rica’s Government. According to the objective of this paper is to develop a wood key identification using macroscopic wood features of 110 species of Northern Caribbean forest. Initially it was described the general characteristics and macroscopic features of each of species. This information was used to build two kind of wood identification keys. The first identification key is presented in graphical form through eleven keys, which describes the main anatomical classification topic and allow species wood identification. The second identification key is a wood dicotomic key, where anatomy features is used as a sorting criterion in two responses. These wood keys identification could be facilitate wood identification by forest guard.